THE ROLE OF PREOPERATIVE INFUSION ON BODY FLUID COMPARTMENTS IN CHILDREN (Herald of the National Children's Medical Center, 2025)
Infusion therapy is an integral part of anesthetic management in pediatric surgery. However, preoperative fluid replacement remains a subject of debate, especially in light of the revised guidelines on fasting before elective procedures. The reduction of preoperative fasting durations calls for an objective assessment of the need for and volume of infusion therapy prior to surgery, aiming to compensate for potential deficits without risking fluid overload.
Keywords: infusion therapy; children; preoperative period; bioimpedance; fluid compartments; Sterofundin G5